2004
DOI: 10.1096/fj.03-1429fje
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B viral HBx induces matrix metalloproteinase‐9 gene expression through activation of ERKs and PI‐3K/AKT pathways: Involvement of invasive potential

Abstract: Hepatitis B virus (HBV) X protein (HBx) has been shown to be essential for the development of hepatocellular carcinoma (HCC). Recently, we have found that HBx causes the progression of liver cancer through down-expression of PTEN, known as a tumor suppressor gene (1). The prognosis for HCC depends mainly on the clinicopathological characteristic regarding invasion and metastasis. The expression of matrix metalloproteinase (MMP)-9 has been implicated as playing an important role in HCC invasion and metastasis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
219
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(238 citation statements)
references
References 61 publications
17
219
1
1
Order By: Relevance
“…In particular, up-regulation of MMP expression has been reported to be dependent on activation of the raf/MEK/ERK signaling pathway, which strictly regulates gene expression (31)(32)(33). Consistently, whereas the high expression of MMP-2 and MMP-9 in C-26 cells correlates with constitutive activation of ERK1/2 protein kinases (Fig.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In particular, up-regulation of MMP expression has been reported to be dependent on activation of the raf/MEK/ERK signaling pathway, which strictly regulates gene expression (31)(32)(33). Consistently, whereas the high expression of MMP-2 and MMP-9 in C-26 cells correlates with constitutive activation of ERK1/2 protein kinases (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…Because the activation of the raf/MEK/ERK signaling pathway has been reported to induce the enhancement of MMP expression (32)(33)(34), the potential influence of Hyp-DCHA on the activity of ERK1/2 was tested. To this purpose, protein lysates of control and treated C-26 cells were subjected to Western blot analysis for phosphorylated (active) as well as total ERK1/2 protein kinases.…”
Section: Hyp-dcha Inhibits Tumor Cell Growth and Survival In Vitromentioning
confidence: 99%
“…Ruhul Amin et al (2003) reported PI3K-Akt was one of the signaling pathways to induce MMP-9 secretion. Recently, hepatitis B viral HBx was shown to induce MMP-9 gene expression through the activation of the ERK and PI3K/Akt pathways (Chung et al, 2004). More importantly, angiogenesis plays an essential role in tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative mechanism for Wnt activation is the repression of E-cadherin transcription through hypermethylation of E-cadherin promoter by activation of DNA methyltranferase 1 (Kanai et al, 1997;Lee et al, 2005b). Recently, studies have shown that HBx may induce cellular migration through activation of matrix metalloproteinase 3 and 9 (Chung et al, 2004;Yu et al, 2005).…”
Section: Hbxmentioning
confidence: 99%